Low Frequency of MKRN3 and DLK1 Variants in Chinese Children with Central Precocious Puberty. (3rd October 2019) - Chen, Ting; Chen, Linqi; Wu, Haiying; Xie, Rongrong; Wang, Fengyun; Chen, Xiuli; Sun, Hui; Xiao, Fei
Abstract : Background . Central precocious puberty (CPP) is defined by gonadotropin-dependent development of secondary sexual characteristics before the age of 8 years in girls and 9 years in boys. MKRN3 and DLK1 are two genes, disease-causing variants of which have recently been discovered to cause idiopathic CPP. Methods . We screened 173 Chinese patients (9 males and 164 females; 9 familial and 164 sporadic) with ICPP and 43 patients (9 males and 34 females; 3 familial and 40 sporadic) with early puberty for variants in MKRN3 . We also screened 19 patients with ICPP and early puberty for variants of DLK1 (17 males and 2 females; 5 familial and 14 sporadic). Results . We identified four novel missense variants of MKRN3, c.1138G > A (p.Glu380Lys), c.1420T > A (p.Leu474Met), c.673C > G (p.Leu225Val), and c.1071C > G (p.Ile357Met) in two sporadic cases and three familial cases. According to ACMG standards, two MKRN3 variant (p.Glu380Lys and p.Ile357Met) are likely pathogenic, and two others are of uncertain significance. We also performed bioinformatic analysis to evaluate the impact of variants on MKRN3 protein structures, which showed that Ile357Met locates at the zinc-binding region (C3HC4 RING finger motif), while Glu380Lys is spatially extremely close to the C3HC4 RING finger, MKRN-specific Cys-His domain, and the third C3H1 zinc-finger motif region. Per Glu380Lys, Glu with negative charges has been changed into Lys with positive charges, which may affect the hydrogen bond formation between amino acids and the stability of the local structure, thus affecting the binding of zinc iron to MKRN3 protein. Besides, we did not identify any variants of DLK1 gene in our patients. Conclusions . In this study, we report four novel MKRN3 variants in patients with ICPP. Moreover, we did not find any variants of DLK1 gene. Variants of MKRN3 are relatively uncommon in Chinese ICPP patients.